1985
DOI: 10.1002/j.1537-2197.1985.tb08471.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and the Rate of Self‐fertilization in a Grape Fern, Botrychium Dissectum

Abstract: Botrychium dissectum is a homosporous fern with bisexual, subterranean gametophytes. Because of these features, B. dissectum would be suspected of displaying a very high frequency of self‐fertilization. Sporophytes collected from three populations of this species were assayed for heterozygosity by determining the electrophoretic mobility patterns displayed by two polymorphic enzymes. Extreme deviations from Hardy‐Weinberg expectations were observed in each population and analyzed by means of F‐statistics. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…(see McCauley et al, 1985;Holsinger, 1987). As intragametophytic selfing results in equilibrium proportions in only one generation (McCauley et al, 1985), the assumption of equilibrium conditions for Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(see McCauley et al, 1985;Holsinger, 1987). As intragametophytic selfing results in equilibrium proportions in only one generation (McCauley et al, 1985), the assumption of equilibrium conditions for Eq.…”
Section: Introductionmentioning
confidence: 99%
“…no selection, genetic drift or microspatial population structuring), Wright's fixation index (F IS ) is equal to the inbreeding coefficient (F e ) and thus can be used to estimate an amalgam of both intergametophytic and intragametophytic selfing in haploid-dominant species with combined sexes and intergametophytic selfing in haploid-dominant species with separate sexes. While many studies have used F IS as an estimate of selfing in homosporous ferns (by assuming that intergametophytic selfing is not present; for example McCauley et al, 1985;Holsinger, 1987), in populations with significant levels of heterozygosity in two unlinked loci, Ritland's (1990) maximum likelihood method can be used to estimate both types of selfing. Low levels of heterozygosity are characteristic of many populations of mosses (Shaw, 2000), and therefore this method has only limited application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In farm P20, F equals 0·26. So if F is interpreted as the proportion of selfed individuals (McCauley et al 1985), that means the parasite on that farm outcrosses 74% of the time.…”
Section: R E S U Lt Smentioning
confidence: 99%
“…Despite this potential selective disadvantage of intragametophytic selfing, electrophoretic studies have indicated high levels of such selfing in Botrychium (McCauley, Whittier and Reilly, 1985; D. Soltis and P. Soltis, 1987a; and Asplenium (Werth, Guttman and Eshbaugh, 1985), and moderate levels in Dryopteris expansa (D. Soltis and P. Soltis, 1987b). Outbreeding seems to occur in most fern species that have been examined (D. Soltis and P. Soltis, 1987a;, as well as lycopod species (P. Soltis and D. Soltis, 1988b) and Equisetum arvense (D. .…”
Section: Introductionmentioning
confidence: 99%